(untitled) (Scientific journal of the Fergana State University, 2023)
Because the word is a very diverse and complex language (speech) unit, its role in our lives is unique, and in the current era of globalization, the development of science, the meaning of the word, the importance of its nominative function, the main purpose of this article is to analyze the classification and interpretations from a specific point of view. The article emphasizes the in-depth study of the word and its logical possibilities. In other words, the conditions of national development in Uzbekistan and the effectiveness of scientific research on our language are the main factors determining our future. Linguistically speaking, the study of the unit of speech analyzes the semantic properties of the word, 4semantic field coverage, onomastic state, denotative and connotative functions in the expression of logic or concept, signifiable and structural forms of these functions.